Theoretical analysis of aqueous residues incineration with oxygen enriched flames - Lacava, P. T.; Pimenta, A. P.; Veras, CAG; Carvalho, J. A. (Elsevier B.V., 1999)
The use of oxygen to enrich the oxidizer can be an attractive alternate to increase incineration rates of a combustion chamber originally designed to operate with air. For a certain fuel now rate, if some incineration parameters are held constant (as combustion chamber temperature, turbulence level, and residence time), an increase of incineration rates becomes possible with injection of oxygen. This work presents a theoretical evaluation of combustion air enrichment in a combustion chamber designed to incinerate aqueous residues using methane as fuel and air as oxidizer. Detailed chemistry was employed to predict pollutants formation. The overall process was investigated using the PSR routine from the CHEMKIN library. (C) 1999 Elsevier B.V. Ltd.